Cardioprotective, antioxidant activities and Phytochemical analysis by GC-MS of Gmelina arborea (GA) in Doxorubicin-induced myocardial necrosis in Albino rats - T.Vijay, M.S. Dhana Rajan, K.Sarumathy, S.Palani, K. Sakthivel (Journal of Applied Pharmaceutical Science)
Doxorubicin (DOX) is a widely used cancer chemotherapeutic agent. However, it generates free oxygen radicals that result in serious dose-limiting cardiotoxicity. Supplementations with Gmelina arborea (Verbenaceae) were proven effective in reducing oxidative stress associated with several ailments. The aim of the current study was to investigate the potential protective effect of Gmelina arborea (GA) against DOX- induced cardiotoxicity in rats. GA was given orally to rats(250&500mg/kg) and DOX (20mg/kg) was administered on the seventh day. GA protected against DOX-induced increased the levels of marker enzymes. It significantly inhibited DOX-provoked glutathione (GSH) depletion in cardiac tissues. The reductions of cardiac activities of catalase (CAT) ,superoxide dismutase (SOD) ,glutathione peroxidase (GSH-Px) and glutathione reductase (GR) were significantly mitigated. Pretreatment of GA significantly guarded against DOX-induced rise of serum lactate dehydrogenase (LDH). GA alleviated histopathological changes in rats’ hearts treated with DOX. In conclusion, GA protects against DOX-induced cardiotoxicity in rats. The study can be attributed, at least in part, to GA’s antioxidant activity.
Keywords: Cardiotoxicity, Doxorubicin, antioxidant, Gmelina arbore, histopathological changes.